Transformation of the Islamic Education System in the Digital Era from a Hadith Perspective - Muhaini, Muhaini; Nursiti Khodijah, Dedek; Wulandari, Febriyantika (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
The transformation of the Islamic education system includes goals, students, curriculum, methods, and infrastructure. In this case, in order to carry out activities in accordance with the guidance of Shara`, we should make the Koran and Hadith the basis for action and treatment in education. Based on the results of the literature study analysis, the transformation of the Islamic Education system in the digital era is justified in Islam as a tool to live life in accordance with existing sharia without having to oppose and deviate from shara`, especially in the implementation of Islamic Education. Therefore, the transformation of the Islamic education system makes the hadith as a basic material considering the educational process carried out by seeing humans as the subject of education, starting with the transformation of Islamic education which starts with the introduction of philosophical theology about humans as a caliph of God on this earth.